2023
DOI: 10.1177/1420326x221148728
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring summertime indoor overheating and pollutant risks and natural ventilation patterns of seniors in public housing

Abstract: Indoor heat and air pollution pose concurrent threats to human health and wellbeing, and their effects are more pronounced for vulnerable individuals. This study investigates exposures to summertime indoor overheating and airborne particulate matter (PM2.5) experienced by low-income seniors and explores the potential of natural ventilation on maintaining good indoor thermal conditions and air quality (IAQ). Environmental and behavioural monitoring and a series of interviews were conducted during summer 2017 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…For each operation condition, the model RMSE and MAE were calculated to quantify the model performance. RMSE and MAE values are shown in Table 8 based on the calculations in Equations ( 9) and (10). For both RMSE and MAE, the lower the value, the better the model fit in general, but each is relative to the number of data points and the units of measure.…”
Section: Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For each operation condition, the model RMSE and MAE were calculated to quantify the model performance. RMSE and MAE values are shown in Table 8 based on the calculations in Equations ( 9) and (10). For both RMSE and MAE, the lower the value, the better the model fit in general, but each is relative to the number of data points and the units of measure.…”
Section: Model Performancementioning
confidence: 99%
“…Prior studies have found that exposures to wildfire smoke increase mortality risk [4], respiratory illness, and cardiovascular mortality [5][6][7][8][9]. Like other types of pollutant exposures, vulnerable populations such as pregnant women, children, and the elderly [10] have higher risks for health effects [11,12]. Some studies have also found that low-income and indigenous populations are at greater risk of adverse effects from indoor exposures to wildfire pollutants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence is formed when airflow is strongly cut on the surface of building walls and vegetation. ENVI-met employs a 1.5 order turbulence closure model to calculate the rate of atmospheric turbulence, by increasing turbulence kinetic energy and dissipation rate, 41,42 as expressed in equations ( 6) and (7).…”
Section: Numerical Modelmentioning
confidence: 99%
“…6 At the same time, the selection of window opening and ventilation time for indoor personnel and the quality of fresh air also directly affect the livability and physical health of residents. 7 Therefore, studying the diffusion and distribution of PM 2.5 in high-density cities is crucial to controlling the harm of particulate matter to human health.…”
Section: Introductionmentioning
confidence: 99%
“…23 Many recent studies indicated that outdoor air is the main source of particulate matter less than 10 microns in size (PM 10 ) in the internal home environment. [24][25][26] The TVOC are another common indoor air pollutants that originate from different internal and external sources. 27,28 The indoor sources of TVOC include smoking, cooking fumes, building materials, furnishers, paints and the use of solvents (such as varnishing), and other office materials (such as adhesives).…”
Section: Introductionmentioning
confidence: 99%